Lived Experiences of Everyday Memory in Adults with Dyslexia: A Thematic Analysis - James Hugo Smith-Spark; Elisa G. Lewis (Behavioral Sciences, 2023)
Dyslexia-related difficulties with memory are well documented under laboratory conditions and via self-report questionnaires. However, the voice of the individual with dyslexia regarding the lived experience of memory across different memory systems and different daily settings is currently lacking. To address this gap in the literature, semi-structured in-depth interviews were conducted with 12 adult female university students with dyslexia. Questions probed different memory systems and experiences across different settings, with interviewees also being asked about their use of technology to support their memory. Two overarching themes were identified in the subsequent thematic analysis. The theme of fallibility of memory had two sub-themes of (i) a lack of trust and confidence in memory and (ii) factors contributing to memory failure. The second theme, facilitators of memory, also consisted of two sub-themes, relating to (i) a preference for traditional tools to support memory and (ii) the use of digital tools to support memory: benefits and limitations. The current study gives insights into the rich and complex extended and distributed cognitive systems of adults with dyslexia. The implications of the findings for dyslexia theory, support in educational and work settings as well as assistive technology development are considered.